H1N1 antibody persistence 1 year after immunization with an adjuvanted or whole-virion pandemic vaccine and immunogenicity and reactogenicity of subsequent seasonal influenza vaccine: a multicenter follow-on study. - Walker, W; de Whalley, P; Andrews, N; Oeser, C; Casey, M; Michaelis, L; Hoschler, K; Harrill, C; Moulsdale, P; Thompson, B; Jones, C; Chalk, J; et al. (2012)
BACKGROUND: We investigated antibody persistence in children 1 year after 2 doses of either an AS03(B)-adjuvanted split-virion or nonadjuvanted whole-virion monovalent pandemic influenza vaccine and assessed the immunogenicity and reactogenicity of a subsequent dose of trivalent influenza vaccine (TIV). METHODS: Children previously immunized at age 6 months to 12 years in the original study were invited to participate. After a blood sample was obtained to assess persistence of antibody against swine influenza A/H1N1(2009) pandemic influenza, children received 1 dose of 2010/2011 TIV, reactogenicity data were collected for 7 days, and another blood sample was obtained 21 days after vaccination. RESULTS: Of 323 children recruited, 302 received TIV. Antibody persistence (defined as microneutralization [MN] titer ≥1:40) 1 year after initial vaccination was significantly higher in the AS03(B)-adjuvanted compared with the whole-virion vaccine group, 100% (95% confidence interval [CI], 94.1%-100%) vs 32.4% (95% CI, 21.5%-44.8%) in children immunized <3 years old and 96.9% (95% CI, 91.3%-99.4%) vs 65.9% (95% CI, 55.3%-75.5%) in those 3-12 years old at immunization, respectively (P < .001 for both groups). All children receiving TIV had post-vaccination MN titers ≥1:40. Although TIV was well tolerated in all groups, reactogenicity in children <5 years old was slightly greater in those who originally received AS03(B)-adjuvanted vaccine. CONCLUSIONS: This study provides serological evidence that 2 doses of AS03(B)-adjuvanted pandemic influenza vaccine may be sufficient to maintain protection across 2 influenza seasons. Administration of TIV to children who previously received 2 doses of either pandemic influenza vaccine is safe and is immunogenic for the H1N1 strain.